PENERAPAN KARTU KATA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS SISWA KELAS I SD ISLAM NU PUNGKURAN TAHUN 2017 - Nurhidayah -; Iswahyudi Joko S; Abdul Karim (Universitas Muhammadiyah Semarang, 2017)
The role of language has significance for the intellectual support of studentsuccess. Teaching language at school is expected to help students introducegood and correct language. Grade 1 students are still aged 6 to 7 years ofstudents interested in drawing so that by introducing the child's writing willmotivate learning. First grade students are in the process of reading andwriting. Teachers need to be aware and done to make the atmospherecomfortable and fun learning. The purpose of this research is to describe the implementation of word card in learning and to know the increase of reading and writing ability of first grade students in SD Islam NU Pungkuran.Implementation of word cards to improve the ability of reading and writingstudents class I. Improvement of learning held on Thursday, September 2, 2017in class I SD Islam NUPungkuran with a total of 13 students. Based on thepercentage of prasiklus results only 38% of students who are able to read andwrite. Improvement of learning cycle I percentage mastery by 62%.Improvements continued in cycle II increased to 77% with a total of 10 students.The researchers concluded that there was a 15% increase from cycle I to cycleII with the number of categories of students able to read and write increasedfrom 8 to 10 students.Keywords: Reading, Writing, and Word Cards